IMPROVING PRIVATE HIGHER EDUCATION PERFORMANCE THROUGH PRACTICES OF KNOWLEDGE MANAGEMENT, LEARNING ORGANIZATION AND TALENT MANAGEMENT - Dewi Lusiana; Rosdiana; Ramaditya, Muhammad (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
The purpose of this study is to identify the organizational performance formation approach used by private universities in Jakarta's LLDikti III neighborhood. Organizational performance is the dependent variable, and knowledge management, learning organizations, talent management, and entrepreneurial mindset are the independent variables. This investigation employs a survey methodology, whereby data is derived using questionnaire-based data gathering outcomes. Lecturers at private universities in the LLDikti III Jakarta region made up the study's population. In this study, 355 respondents made up the sample. SmartPLS with SEM (Structural Equation Modeling) based on PLS (Partial Least Square) is the analysis tool utilized. The study's findings indicate that while learning organizations are unaffected by knowledge management, organizational performance.